Evolutionary creation in biblical and theological perspective - Lioy, Dan (Studies in biblical literature, 2011)
Prologue -- An evolutionary creationist process for the origin of humanity -- The prescientific cosmology found in the Old and New Testaments -- A biblical and theological analysis of life and death in Old Testament -- A biblical and theological analysis of life and death in nNew Testament -- Progressive covenantalism as an integrative motif of Scripture -- Epilogue